(3GdLhGgQ GdeLehYI hGdfhGOQ GdeSehYIs - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdeYQha GdYGe hGdaVd GdPi dG EfJgGA dg agPG cJGH fajS eNJUQ ef GdMOjK GdfHhi hGdCKQ ai eOM GdSNGA hGdcQe s
(3BNQgG (B:s
(3hbGd (B: (3hgH GHf efHg Ef CMSf GdfGS YjTkG ef MSf YjT GdfGS ai YjTI Gddge ELYdfG eKfjf dfYeJc TGcQjf dgG bGHdjf HgG BNQ GdLhGgQ GdeLehYI hGdfhGOQ GdeSehYI s
(3HgG fXGe GdJYbjHIs
(3eNJUQ ef GdMOjK GdfHhi hGdCKQ ai eOM GdSNGA hGdcQe hPe GdHNd heG jYbHI ef GdfOe hTF eeG Mci Yf GdcQeGA hGdHGNdjf hGdMV Ydi GdJUOb haYd GdeYQhas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
Keywords: (3GdMOjK h GdeUWdMs